Vers une méthode de réhabilitation des grands ensembles plus respectueuse des habitants et des valeurs d’usages. Le cas d’Ancely, à Toulouse - Natacha Issot (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Housing estates’ transformations are today made without taking into account what makes the identity of the place. Nevertheless the housing estate are composed with materials and immaterial elements which are they own. Habitants, users, by their practices are the first witnesses of needs, challenges, and history of the housing estate. Use knowledge and place analysis are a base for a diagnostic and for more respectful transformations of heritage quality and use value.